Groin defect reconstruction with perforator flaps: Considerations after a retrospective single-center analysis of 54 consecutive cases. Issue 11 (November 2019) - Arvanitakis, Michael; Schlagnitweit, Paul; Franchi, Alberto; Fritsche, Elmar; Chen, Yen-Chou; Scaglioni, Mario F.
Summary: Introduction: Groin defects with exposed complex structures are challenging to treat. Perforator flaps provide a contemporary alternative to established muscle flaps to cover all varieties of groin defects, with minimum donor site morbidity, less postoperative pain, and faster rehabilitation. In this retrospective single-center analysis, we aimed to show that pedicled perforator flaps are a valid option for groin defect reconstruction. We present three different pedicled perforator flaps and discuss the flap selection process and their distinct advantages and disadvantages. Methods: A series of 54 consecutive cases of patients with groin defects were allocated into three different treatment groups. Reconstruction was performed utilizing the anterolateral thigh (ALT) flap, the pedicled posteromedial thigh (PMT) perforator flap, and the vertical deep inferior epigastric artery perforator (vDIEP) flap. Results: All 54 flaps survived. Early complications included one hematoma (vDIEP) and two infections (ALT and PMT). Delayed complications occurred in three recipient-site seromas (ALT, PMT, and vDIEP), one donor-site seroma (vDIEP), and one flap dehiscence (ALT). All flaps provided stable coverage during 3–12 months of follow-up. Conclusion: We propose pedicled perforator flaps to be a safe and reliable option for groin defect reconstruction. The pedicled PMT flap should be the first choice if the profunda femoris artery and its perforators are available. The ALT flap can be applied as a second choice, especially if complex groin defect with exposed vascular prosthesis reconstruction is needed because of its versatile expansion options, for example, as a chimeric flap using a portion of the vastus lateralis muscle. In cases where the profunda femoris artery is not available, the vDIEP flap should be the preferred method.